A review of the genus Entisberus Distant (Hemiptera: Heteroptera: Rhyparochromidae: Drymini) - Scudder, G.g.e. (Zootaxa, 2016)
The genus Entisberus Distant is reviewed and illustrated and diagnostic characters listed. The type species, E. archetypus Distant is illustrated and diagnostic characteristics noted. The female of E. bergrothi Kondorosy is described for the first time. A new species, E. interruptus from Mindanao [Island] in the Republic of the Philippines, is described, and a revised key to the species of Entisberus is given.